Pinworm (Enterobius vermicularis) Infection in Children of Barbhanjyang VDC, Tanahun District, Nepal - Dahal, Tara; Maharjan, Mahendra (Journal of Institute of Science and Technology, 2015)
The present study was carried out to determine the prevalence of Enterobius vermicularis in children of Barbhanjyang Village Development Committee, Tanahun, District, Nepal. A total of 110 Scotch tape (Cellophane tape) samples of children aged between 1-12 years were collected and microscopically examined. Altogether 14(12.72%) enterobias prevalence cases were reported in children including sixteen percent male and nine percent female cases. High prevalence of pinworm infection was the age group of 5-8 years (5.45%). The infection rate was significantly associated with ethnic groups (?2 =11.824, df=2, P=0.003) since the prevalence rate was highest in Dalit children (64.28%) compared to others. Itching behaviour of children around the perianal regions was directly associated with the prevalence rate of the pinworm (P=0.0325). Nail biting habit of children was also found to be statistically significant (P=0.024). Journal of Institute of Science and Technology, 2015, 20(2): 18-21